Serious Games Second Joint International Conference, JCSG 2016, Brisbane, QLD, Australia, September 26-27, 2016, Proceedings - Marsh, Tim; Ma, Minhua; Oliveira, Manuel Fradinho; Baalsrud Hauge, Jannicke; Göbel, Stefan (Information Systems and Applications, incl. Internet/Web, and HCI, 2016)
This book constitutes the proceedings of the Second Joint International Conference on Serious Games, JCSG 2016, held in Brisbane, QLD, Australia, in September 2016. This conference bundles the activities of the International Conference on Serious Games Development and Applications, SGDA, and the Conference on Serious Games, GameDays. The total of 36 full papers and 5 short papers was carefully reviewed and selected from numerous submissions. The papers were organized in topical sections named: health, well-being and accessibility; education, learning and training; science, nature and heritage; design, development and analysis; poster papers; exhibits.